Perancangan Single Girder Gantry Crane 2 Ton di PT Spindo Unit VI - Saputra, Yudi Kurniawan; Arizal, Heru (Jurnal Mesin Nusantara, 2023)
In carrying out the design process, the main factor that must be considered is the lifting strength of the crane against the maximum load borne. Because the inaccuracy of the design process can result in malfunctions, even causing work accidents. Therefore, it is necessary to do the right design so that it can be used safely. In this design, the design of a lifting aircraft with a single girder gantry crane is designed with a lifting capacity of up to 2 tons, a lifting height of 4 meters, and a transfer width of 5 meters.. The design method used is by substituting the values ​​and other factors needed into the known equations to obtain the final result. To determine the maximum tensile strength of the load in this crane design, the equation for the maximum tensile force is used to obtain a result of 633.12 kg. Then for the steel rope chosen in this design is the 222 wire construction with parallel positions. By using the equation for resistance of the motor to movement, the power needed to move the crane is also 23,215 HP